Utilization of early postnatal care services and associated factors among mothers who gave birth in the last 12 months in South Gondar Zone District, Amhara Regional State, Ethiopia - Tigist Seid Yimer; Wassie Yazie Ferede; Fillorence Ayalew Sisay (Journal of Health, Population and Nutrition, 2024)
Abstract Introduction Postnatal care is care that is provided to mothers and newborn baby after delivery. The care given after childbirth is the most critical time because most maternal and neonatal mortality occurs during this period. Utilization of this service is low in Ethiopia, and no evidence exists to describe the status of early postnatal care service utilization among women in the study area. Objective This study aimed to assess the utilization of early postnatal care services and associated factors among mothers who gave birth in the last 12 months in the South Gondar Zone District, Amhara Region, Ethiopia, in 2021. Method This study was conducted in South Gondar Zone Districts from October 1 to 30, 2021. A total of 761 participants were included in this study using a simple random sampling method. The study participants were mothers who gave birth in the last 12 months. The data were collected via interview-guided semistructured questionnaires. The collected data were coded and entered into EPI Info version 7.2 and exported into SPSS version 23 for analysis. Both binary and multivariate logistic regression analyses were applied to identify factors affecting the outcome variables. The results of the final model are presented as the adjusted odds ratio (AOR) and 95% confidence interval (CI). A P value less than 0.05 was considered to indicate statistical significance. Results In this study, 761 mothers participated, for a response rate of 100%. The overall prevalence of early utilization of postnatal care services was 20.6%. Mothers who live in urban areas were five times more likely to have early visits than those living in rural areas with adjusted odds ratio [AOR (95% CI) = 5.2 (3.19, 8.54)], a mothers who had a history of more than four parity had more likely to visit than the others at [AOR (95% CI) = 2.25 (1.18, 4.29)], mothers who had a history of pregnancy had two times more likely to visit than the other [AOR (95% CI) = 2.06 (1.05, 4.05)], and mothers who had delivered by instrumental vaginal delivery or cesarean section delivery and those mothers who had mass media exposure were two and five times more likely to visit, respectively [AOR (95% CI) = 2.62 (1.40, 4.91)] and [AOR (95% CI) = 5.18 (2.55, 10.52)]. Conclusion and recommendation Compared with those of other studies, the overall prevalence of early utilization of postnatal care services was low. Improving mothers’ knowledge of early postnatal care visits is very important for enhancing quality of life and minimizing neonatal and maternal morbidity and mortality.